IMPLEMENTATION OF LAND DISPUTE SETTLEMENT BY VILLAGE HEAD TOWARDS VILLAGE COMMUNITY (STUDY OF RANDUATI VILLAGE, NGULING DISTRICT, PASURUAN REGENCY) - A. Jalalludin; Misranto; Diyan Isnaeni (Pena Cendekia Insani, 2025)
This study focuses on the preferences of the Randuati Village community towards informal mediation mechanisms by the village head in resolving land disputes. Using a qualitative approach with a case study method, data were obtained through in-depth interviews and participatory observations. The results of the study indicate that the choice of informal mediation is not only due to limited access to the formal legal system, but further reflects collective trust in the social and historical authority of the village head. This confirms the existence of legal pluralism, where formal law and local law not only coexist but also influence each other in the practice of conflict resolution. The village head acts as a legal broker who bridges state law with the law that lives in society. The implications of this finding emphasize that justice at the grassroots level is the result of a complex interaction between norms, culture, and social structures. This study makes an important contribution to the development of more contextual and community-based agrarian policies, as well as opening up space for strengthening local mediation systems that are responsive to community needs.